The Effect of Using Duolingo Application on Students’ English Learning Motivation and Vocabulary Enrichment : An Experimental Research at SMKN 1 Padang - Vinni Nasrul; Sitti Fatimah (Universitas Negeri Padang, 2023)
This research aimed to determine the effect of using Duolingo application on English learning motivation and vocabulary enrichment for the 10th grade students at SMKN 1 Padang. This research used a Quantitative Research Method which is pre-experimental. The population of this research was the 10th grade students at SMKN 1 Padang, which was X TKP A is the experiment class and the total sample was 22 students. The data collection techniques were motivation questionnaire and vocabulary enrichment test. The results of the study used IBM SPSS Statistics 29.0.1.0. and also Paired Sample T-Test formula was used by researcher to analyze the data. The Mean score for motivation before using Duolingo is 47.86 and after using it is 81.82. Then, the mean for vocabulary enrichment students before using Duolingo is 48.91 which is higher than the mean score after using it is 82.50. The result shows there is a positive effect of English learning motivation and vocabulary enrichment students through using Duolingo. Thus, both of the sig. score = < .001 which means it is smaller than α.005. So, the alternative hypothesis (Ha) for English learning motivation and vocabulary enrichment for the 10th grade students were accepted and those null hypothesis (Ho) were rejected in this research. In addition to this result, using the Duolingo Application had significant effect for the 10th grade students on English learning motivation and vocabulary enrichment in teaching-learning activities in classroom.